Work Life Balance in ICT Sector in Ahmadabad - Bhoomika D. Bhatt (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
“Work-Life Balance" is abbreviated as WLB. This study explores it among the Employees Working in the ICT Sector. It is based on a Questionnaire of 33 Questions, in Google Docs and the Respondents’ replies. It is an overview on “Work-Life Balance”, a small but vital meditation on one of the burning issues in the area of the human resource management. Within its confines, this study strives to dig out some home truths about the straining circumstances and situations that most of the employees undergo while maintaining the balance with life. It succinctly tries to bring forth some factual details on the basis of the real-life situations. An employee, whether in ICT or other sectors, is a human being, and has his/her family, life and other responsibilities to perform in a family, in a society and among his friends.